2022
DOI: 10.3390/cancers14143392
|View full text |Cite
|
Sign up to set email alerts
|

Zero Setup Margin Mask versus Frame Immobilization during Gamma Knife® Icon™ Stereotactic Radiosurgery for Brain Metastases

Abstract: We compared the clinical outcomes of BM treated with mask immobilization with zero-SM (i.e., zero-PTV) to standard zero-SM frame immobilization SRS. Consecutive patients with BM, 0.5–2.0 cm in maximal diameter, treated with single-fraction SRS (22–24 Gy) during March 2019–February 2021 were included. Univariable and multivariable analysis were performed using the Kaplan–Meier method and Cox proportional hazards regression. A total of 150 patients with 453 BM met inclusion criteria. A total of 129 (28.5%) lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“… 66 Based on the importance of the precision of the targeting in these small tumors, important considerations for patient immobilization should include patient comfort, end-to-end accuracy testing, whether a set-up margin is added to the volume, and overall time treatment. 67 , 68 …”
Section: Discussionmentioning
confidence: 99%
“… 66 Based on the importance of the precision of the targeting in these small tumors, important considerations for patient immobilization should include patient comfort, end-to-end accuracy testing, whether a set-up margin is added to the volume, and overall time treatment. 67 , 68 …”
Section: Discussionmentioning
confidence: 99%
“…A PTV margin can be added to the CTV to prevent geographic misses and allow for geometric errors in radiation therapy [17]. Contrastingly, conventional SRS involves rigid immobilization fixation of a single fraction with GK using a 0 mm PTV with no margin, similar to surgical excision of brain targets [18,19]. Previous studies have reported contradictory results for using the PTV margin to account for geometric uncertainty.…”
Section: Introductionmentioning
confidence: 99%